2017
DOI: 10.1007/s10068-017-0116-0
|View full text |Cite
|
Sign up to set email alerts
|

Erythritol production by Yarrowia lipolytica mutant strain M53 generated through atmospheric and room temperature plasma mutagenesis

Abstract: Mutants of with high erythritol production were generated through an atmospheric and room temperature plasma (ARTP) mutation system. Among these mutants, M53 exhibited the highest erythritol yield. In a batch culture, M53 produced 64.8 g/L erythritol from 100 g/L glycerol. The yields of byproducts (e.g. mannitol, arabitol, and α-ketoglutaric acid) were low, and the mechanisms underlying these changes were examined by measuring enzyme activities in the pentose phosphate pathway. Up to 145.2 g/L erythritol was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Cells of Y. lipolytica SWJ‐1b were treated using atmospheric and room temperature plasma method (helium gas flow rate: QHe = 10 standard liters per minute, radio frequency power: 120 W, treatment time: 2 min), and the obtained mutants were then screened for high erythritol production strains. Y. lipolytica M53 could produce 0.65 g/g glycerol of erythritol or 0.54 g/g glycerol of citric acid respectively under different culture condition and was selected as the research strain . M53 was grown on yeast peptone dextrose agar slant with 10.0 g/L of yeast extract, 20.0 g/L of peptone, 20.0 g/L of glucose, and 20.0 g/L of agar.…”
Section: Methodsmentioning
confidence: 99%
“…Cells of Y. lipolytica SWJ‐1b were treated using atmospheric and room temperature plasma method (helium gas flow rate: QHe = 10 standard liters per minute, radio frequency power: 120 W, treatment time: 2 min), and the obtained mutants were then screened for high erythritol production strains. Y. lipolytica M53 could produce 0.65 g/g glycerol of erythritol or 0.54 g/g glycerol of citric acid respectively under different culture condition and was selected as the research strain . M53 was grown on yeast peptone dextrose agar slant with 10.0 g/L of yeast extract, 20.0 g/L of peptone, 20.0 g/L of glucose, and 20.0 g/L of agar.…”
Section: Methodsmentioning
confidence: 99%
“…Beside this, atmospheric and room temperature plasma mutagenesis was also used to generate mutants of Y. lipolytica with increased EOL productivity. With such a mutant strain (M53), glycerol fed-batch cultivation in a 5 L bioreactor led to an EOL titer of 169.3 g/L within 168 h with a yield of 0.65 g/g [108]. Figure 2.…”
Section: Erythritolmentioning
confidence: 99%
“…Fermented okara is a soybean residue, which was used as a feedstock for the production of EOL by mutant strain M53. This allowed an EOL titer of 14.7 g/L with a yield of 0.49 g/g in a 5 L bioreactor within 144 h [108]. By overexpressing SUC2 genes from Saccharomyces cerevisiae encoding invertase and native GUT1 gene (YALI0F00384g), encoding glycerol kinase (GK), EOL was produced from raw industrial molasses (60 g/L) and crude glycerol (100 g/L) and reached a titer of 100 g/L with a productivity and yield of 1.1 g/(L•h) and a yield of 0.67 g/g [109].…”
Section: Erythritolmentioning
confidence: 99%
“…For example, Zhao et al utilized plasma discharge to mutate a polyunsaturated fatty acids producing strain of Schizochytrium sp [ 40 ]. Liu et al obtained a Yarrowia lipolytica M53 strain with high glycosyl alcohol content by plasma discharge mutagenesis [ 41 ]. Li et al showed that after Aspergillus terreus was treated with ARTP mutagenesis, it reached a higher itaconic acid yield of 19.3 g/L with 36.01% sugar conversion [ 42 ].…”
Section: Introductionmentioning
confidence: 99%